2004
DOI: 10.1080/00016470410001484
|View full text |Cite
|
Sign up to set email alerts
|

Positive pivot shift after ACL reconstruction predicts later osteoarthrosis63 patients followed 5–9 years after surgery

Abstract: Background Rupture of the anterior cruciate ligament (ACL) may cause osteoarthrosis (OA) and functional impairment. We wanted to find out whether the degree of knee stability obtained after ACL reconstruction correlates with radiographic and clinical outcome.Patients and methods We examined 63 patients 2 and 5-9 years after anterior cruciate ligament (ACL) reconstruction. Knee stability was assessed 2 years after surgery by recording AP laxity using radiostereometric technique (RSA) and by performing the pivot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
208
1
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(222 citation statements)
references
References 19 publications
5
208
1
7
Order By: Relevance
“…Patients having a negative pivot shift test showed significantly less signs of radiographic osteoarthritis and better functional assessment scores independent of reconstruction. This is in line with the results published by Jonsson et al [15] who suggested a positive pivot shift test as predictor of later osteoarthritis based on the results of a long-term radiographic evaluation. Also Kocher et al reported a significant relationship between the pivot shift test grades and patient satisfaction, whereas anterior posterior laxity did not have influence on patient subjective assessment two years postoperatively [16].…”
Section: Discussionsupporting
confidence: 82%
“…Patients having a negative pivot shift test showed significantly less signs of radiographic osteoarthritis and better functional assessment scores independent of reconstruction. This is in line with the results published by Jonsson et al [15] who suggested a positive pivot shift test as predictor of later osteoarthritis based on the results of a long-term radiographic evaluation. Also Kocher et al reported a significant relationship between the pivot shift test grades and patient satisfaction, whereas anterior posterior laxity did not have influence on patient subjective assessment two years postoperatively [16].…”
Section: Discussionsupporting
confidence: 82%
“…Correlations with clinical outcome, as well as with the development of OA [121][122][123], further emphasize the importance of this concept. Consequently, a variety of technical tools focus on objectifying the pivot shift.…”
Section: Assessment Of Rotatory Laxitymentioning
confidence: 99%
“…This is due to the fact that the presence of a pivot-shift phenomenon after ACL reconstruction is associated with functional impairment and consequently poor patient satisfaction [5,6]. In addition, according to the report from Jonsson et al [7], patients with positive pivot-shift findings demonstrated increased scintigraphic activity in the subchondral bone of the knee joint [7]. Furthermore, negative pivot shift test demonstrated fewer signs of radiographic osteoarthritis [8].…”
Section: Introductionmentioning
confidence: 99%